HAEMATOLOGICAL AND BIOCHEMICAL ALTERATIONS OF CATLA CATLA FINGERLINGS FOLLOWING SUBLET EXPOSURE TO NUVAN - MEDDA, CHIRANJIB (Journal of Indian Fisheries Association, 2015)
The sublethal exposure (0.24 ppm) of Nuvan on some biochemical compositions such as serum protein, blood glucose, glutamate oxaloacetate transaminase (AST) and glutamate pyruvate transaminase (ALT) and on some haematological parameters such as red blood corpuscles (RBC), white blood corpuscles (WBC), haemoglobin content (Hb), mean corpuscular concentration (MCV), mean corpuscular haemoglobin concentration (MCHC) of Calla calla fingerlings were studied. The haematological and biochemical parameters evoked a significant reduction (excepting MCV, ALT and AST which is significantly increased) with increasing days of Nuvan exposure